TINGKAT PEMAHAMAN NASABAH TENTANG AKAD MURABAHAH DAN PENGARUHNYA TERHADAP MINAT BERINVESTASI DI BANK SYARIAH - Suharta, Suharta; Khotimah, Umi Khusnul; Hidayat, Hidayat; Ramadhan, Taufiq (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2021)
Indonesian people's understanding of murabahah products in Islamic banks is still uneven. In January 2020, the Murabahah contract had the largest portion in Indonesian Islamic banking, which was around 58%, while the musyarakah contract was 39.5% and the mudharabah contract was 2.5%. The main problem in this study is how high the level of understanding of Bank Syariah Mandiri and BTN Syariah Serang customers on murabahah buying and selling, and whether the level of customer understanding can affect investment in Bank Syariah Mandiri and BTN Syariah bank Serang Banten. The author collected primary data with field research with a quantitative descriptive approach, with a questionnaire to 100 customers of Bank Syariah Mandiri and Bank BTN Syariah Serang Banten. The results of this study show: First, customers of Bank Syariah Mandiri Serang have an understanding level of 97.4%, while customers of BTN Syariah Bank Serang have an understanding level of 95.2%. Second, the opinion of customers who think that the level of understanding can affect the interest in investing in Islamic banks is 93.8% for Mandiri Syariah Bank customers, and BTN Syariah Bank customers are 95.3%.